RETRACTED: STUDI METODOLOGI TAFSIR SURAT YASIN KARYA MUḤAMMAD IRSYAD - Nafisah; Masruchan (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2022)
Following careful and considered review of the article entitled “Studi Metodologi Tafsir Surat Yasin Karya Muḥammad Irsyad”, Published in the Revelatia: Jurnal Ilmu Al Qur’an dan Tafsir Vol. 3 No. 1 (2022), by Nafisah and Masruchan lecturer at the Sunan Ampel State Islamic University Surabaya. This article has been retracted at the request of the Editor-in-Chief. The author has plagiarized parts of the following papers: Fawaidur Ramdhani, “ Apologetika tafsir al Qur’an: tipologi tapsèr sorat Yaa Siin Bhasa Madhura karya Muhammad Irsyad.” Undergraduate thesis, UIN Sunan Ampel Surabaya. http://digilib.uinsby.ac.id/21906/ Fawaidur Ramdhani and Ahmad Zaidanil Kamil, “Tafsir Alquran Bahasa Madura: Mengenal Tapsèr Sorat Yaa-siin (BhasaMadhura) Karya Muhammad Irsyad” DOI: https://doi.org/10.32495/nun.v5i1.103 One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.